Critical Review of the Constitutional Court’s Decision on the Presidential Threshold: Tinjauan Kritis Mengenai Putusan Mahkamah Konstitusi tentang Ambang Batas Pencalonan Presiden - Sukmawan, Denny Indra; Pratama, Syaugi (Jurnal Konstitusi, 2023)
This article aims to enrich the literature on the threshold for presidential candidacy in Indonesia by: Firstly, summarizing the main criticisms of its implementation; Secondly, refuting the arguments of the Constitutional Court regarding the threshold’s potential to increase political support for the elected President and reduce the number of political parties. This research employs a qualitative methodology, utilizing a literature study design and case studies involving the Constitutional Court’s decisions on the presidential candidacy threshold, along with previous studies on the relationship between political parties and the President. In general, we have found that the primary criticisms of setting the presidential candidacy threshold revolve around its potentially unconstitutional implementation and its contribution to political oligarchy. In practice, setting the presidential candidacy threshold is entirely unrelated to an increase in political support for the President and cannot reduce the number of political parties.